Variasi Konsentrasi Ekstrak Mahkota Bunga Kasumba Turate (Carthamus tinctorius L.) dan Ekstrak Etanol Umbi Bawang Dayak (Eleutherine palmifolia) sebagai Imunostimulan - Yuri Pratiwi Utami (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Fagocytosis is a process characterized by phagocytic cells ingesting good, pathogenic foreign cells commonly carried out by macrophages. This study aimed to determine the phagocytic activity of a combination of crown extract of turate kasumba (Carthamus tinctorius L.) and dayak onion tuber extract (Eleutherine palmifolia) as immunostimulant. The study was experimental, the number of mice used in the test was 21 individuals and randomly divided into 7 groups (n = 3); K1 was given C. tinctorius extract 1% w/v; K2 was given E. palmifolia extract 2% w/v; K3 was given E. palmifolia extract 4% w/v; K4 and K5 was given syrup combination C. tinctorius and E. palmifolia extract = 1 : 2 and 1 : 4% w/v; K6 was given Stimuno®; while K7 as negative control. Phagocytic activity was carried out on the 11th day using the carbon cleaning method. The results showed that the highest phagocytic activity was shown by K4 significant (p <0.05) on K1, K2, K3, K5, K6, and K7. This shows that K4 has better immunostimulatory activity than other groups.